KONTRIBUSI PERSEPSI TENTANG KEPEMIMPINAN PEREMPUAN TERHADAP WORK ENGAGEMENT KARYAWAN BANK BNI BUKITTINGGI - Riri Afrizeni (Jurnal Riset Psikologi, 2018)
Abstract: Contribution perceptions about women's leadership to work engagement BNI Bukittinggi This study aims to determine the contribution between perceptions on women's leadership to work engagement on the employees of Bank Negara Indonesia, Bukittinggi. The research design used quantitative correlation. The population in this study is employees of BNI Bank in all branch offices of Bukittinggi. The technique of collecting samples using Purposive Sampling with the number of samples of 40 people who are divided from 8 female superiors. This research uses perception scale on female leadership with reliability value 0.946 and work engagement scale with reliability value 0.897. Data analysis using simple linear regression analysis technique. Based on the results of hypothesis testing obtained value of F = 65.821 and p = 0.000 (p <0.01) with the value of correlation coefficient (r) = 0.796 shows the perception on the leadership of women contribute to work engagement.Keywords: Women's leadership, work engagement, perceptionAbstrak: Kontribusi persepsi tentang kepemimpinan perempuan terhadap work engagement karyawan Bank BNI Bukittinggi. Penelitian ini bertujuan untuk mengetahui kontribusi antara persepsi pada kepemimpinan perempuan terhadap work engagement pada karyawan Bank BNI Bukittinggi. Desain penelitian yang digunakan kuantitatif korelasional. Populasi dalam penelitian ini karyawan bank BNI di semua kantor cabang Bukittinggi. Teknik pengumpulan sampel menggunakan Purposive Sampling dengan jumlah sampel sebanyak 40 orang yang terbagi dari 8 atasan perempuan. Penelitian ini menggunakan skala persepsi pada kepemimpinan perempuan dengan nilai reliabilitas 0.946 dan skala work engagement dengan nilai reliabilitas 0.897. Teknik analisis data menggunakan teknik analisis regresi linier sederhana. Berdasarkan hasil pengujian hipotesis diperoleh nilai F=65.821 dan p=0.000 (p<0.01) dengan nilai koefisien korelasi (r)=0.796 menunjukkan persepsi pada kepemimpinan perempuan berkontribusi terhadap work engagementKata kunci: Kepemimpinan perempuan, work engagement, persepsi